Kajian Peran Cyber Law Dalam Memperkuat Keamanan Sistem Informasi Nasional - Darmawan Napitupulu (Universitas Budi Luhur, 2017)
Increasingly increasing the Information Technology also positive and negative impact. The positive aspect of this virtual world of course adds to the trend of world technological development with all forms of human creativity. In addition, the negative impact can lead to the emergence of crime called cyber crime or crime through the Internet network. The increasingly widespread crime that is closely related to the use of computer-based technology and telecommunication networks is increasingly making the Internet network users become uneasy. The most important information system security policy is in the national legal order in the form of Cyber Law in this case the related ITE and Criminal Law regulating cyberspace activities including sanctions on adverse activity. The research method used is the study of the library (desk research) related to the role of cyber law and its application approach in Indonesia. The results show that the role of cyber law in strengthening the security of national information systems is very strategic. With the existence of cyber caw in addition to protecting the public or the public nationally from the threat of cyber crime, cyber law is a tool to convince the international community that there is already a firm regulation on cyber defense in the country so that inter-state cooperation can be established in building global security. Cooperation between countries is expected also able to trigger a stronger regulation and give global effect.